Risk Factors for Left Ventricular Thrombus Formation in Patients with Dilated Cardiomyopathy - Wu, Hao-Sheng; Dong, Jian-Zeng; Du, Xin; Hu, Rong; Jia, Chang-Qi; Li, Xu; Wu, Jia-Hui; Ruan, Yan-Fei; Yu, Rong-Hui; Long, De-Yong; Ning, Man; Sang, Cai-Hua; Jiang, Chen-Xi; Bai, Rong; Wen, Song-Nan; Liu, Nian; Li, Song-Nan; Wang, Wei; Guo, Xue-Yuan; Zhao, Xin; Zuo, Song; Cui, Yi-Kai; Tang, Ri-Bo; Ma, Chang-Sheng (Seminars in Thrombosis and Hemostasis, 2022)
Background Left ventricular thrombus (LVT) is a common complication of dilated cardiomyopathy (DCM), causing morbidity and mortality.Methods This study retrospectively analyzed patients with DCM from January 2002 to August 2020 in Beijing Anzhen Hospital. Clinical characteristics were compared between the LVT group and the age and sex 1:4 matched with the LVT absent group. The receiver operator characteristic (ROC) curve was plotted to evaluate the diagnostic value of D-dimer predicting LVT occurrence in DCM.Results A total of 3,134 patients were screened, and LVT was detected in 72 (2.3%) patients on echocardiography. The patients with LVT had higher D-dimer, fibrinogen, and lower systolic blood pressure than those without LVT. The ejection fraction (EF) was lower and left ventricular end-systolic diameter was larger in the LVT group. Severe mitral regurgitation (MR) was more common in the LVT absent groups. The prevalence of atrial fibrillation was lower in the LVT group. The ROC curve analysis yielded an optimal cut-off value of 444 ng/mL DDU (D-dimer units) for D-dimer to predict the presence of LVT. Multivariable binary logistic regression analysis revealed that EF (OR = 0.90, 95% CI = 0.86–0.95), severe MR (OR = 0.19, 95% CI = 0.08–0.48), and D-dimer level (OR = 15.4, 95% CI = 7.58–31.4) were independently associated with LVT formation.Conclusion This study suggested that elevated D-dimer levels (>444 ng/mL DDU) and reduced EF were independently associated with increased risk of LVT formation. Severe MR could decrease the incidence of LVT.
Keywords: dilated cardiomyopathy; D-dimer; left ventricular ejection fraction; left ventricular thrombus; mitral regurgitation